A brief assessment of capacity to consent instrument in acutely intoxicated emergency department patients - Martel, Marc L.; Klein, Lauren R.; Miner, James R.; Cole, Jon B.; Nystrom, Paul C.; Holm, Kayla M.; Biros, Michelle H. (The American journal of emergency medicine, 2018)
The aim of this study was to determine to what extent acute alcohol intoxication effects capacity to assent, consent, or refuse research participation. This was a prospective, observation study performed at our inner city, county hospital with >100,000 annual emergency department visits. Non-pregnant, English speaking patients older than 18 with evidence of acute alcohol intoxication were considered eligible. After medical screening, a trained research associate presented the study version of the University of California, San Diego Brief Assessment of Capacity to Consent (UBACC) tool. The primary outcome was the number of patients able to correctly respond to all 10 questions. Of 642 screened patients, 415 patients were enrolled and completed the tool. The mean alcohol concentration was 227mg/dL (range 25–500mg/dL). Sixteen patients (3.9%) answered all 10 questions correctly; by definition of the UBACC, these patients were deemed to possess capacity to consent. Mean alcohol concentrations in the capacity group were lower than in those lacking capacity; 182mg/dL (SD 6.7) versus 229mg/dL, (SD 7.9). Of the 287 patients who were interviewed upon sobriety at discharge, 182 patients (63.4%) did not recall completing the questionnaire. While intoxicated emergency department patients are able to complete the questionnaire, the majority do not possess capacity to provide informed consent to research. A minority of participants remember involvement once they have achieved sobriety, exception from informed consent protocols are needed to perform emergency research in this population.